Effect of Dietary Zinc Methionine Supplementation on Growth Performance, Immune Function and Intestinal Health of Cherry Valley Ducks Challenged With Avian Pathogenic Escherichia coli - Chang, Yaqi; Mei, Jia; Yang, Ting; Zhang, Zhenyu; Liu, Guangmang; Zhao, Hua; Chen, Xiaoling; Tian, Gang; Cai, Jingyi; Wu, Bing; Wu, Fali; Jia, Gang (Frontiers in Microbiology, 2022)
The study was carried out to evaluate the effects of supplemental zinc methionine (Zn-Met) on growth performance, immune function and intestinal health of meat ducks challenged with avian pathogenic Escherichia coli (APEC). A total of 480 one-days-old Cherry Valley male ducks were randomly assigned to 8 treatments with 10 replicates, each replicate containing 10 ducks. A 4 ×2 factor design was used with four dietary zinc levels (0, 30, 60, 120 mg Zn/kg in the form Zn-Met was added to the corn-soybean basal diet) and challenged with or without APEC at 8-days-old. The trial lasted for 14 d. Results showed that dietary Zn-Met supplementation significantly increased body weight of 14 days and body weight gain, and decreased mortality during 7-14 d of ducks (P < 0.05). Furthermore, dietary Zn-Met supplementation noticeably increased the thymus index at 2 DPI and 8 DPI (P < 0.05), and enhanced the serum IgA at 2 DPI and IgA, IgG, IgM, C3 at 8 DPI (P < 0.05). In addition, dietary Zn-Met supplementation dramatically increased VH and V/C of jejunum at 2 DPI and 8 DPI (P < 0.05). The TNF-α and IFN-γ mRNA expression were downregulated after supplemented with Zn-Met in jejunum at 8 DPI (P < 0.05). Moreover, dietary Zn-Met supplementation stimulated ZO-3, OCLN mRNA expression at 2 DPI and ZO-2 mRNA expression in jejunum at 8 DPI (P < 0.05), and improved the MUC2 concentration in jejunum at 2 DPI and 8 DPI (P < 0.05). At the same time, the cecal Bifidobacterium and Lactobacillus counts were increased (P < 0.05), and Escherichia coli counts were decreased (P < 0.05) after supplemented with Zn-Met. In conclusion, inclusion of 120 mg/kg Zn-Met minimizes the adverse effects of APEC challenge on meat ducks by improving growth performance and enhancing immune function and intestinal health.